Trade‐off between taxon diversity and functional diversity in European lake ecosystems. Issue 23 (14th November 2016) - Grossmann, Lars; Beisser, Daniela; Bock, Christina; Chatzinotas, Antonis; Jensen, Manfred; Preisfeld, Angelika; Psenner, Roland; Rahmann, Sven; Wodniok, Sabina; Boenigk, Jens
Abstract: Inferring ecosystem functioning and ecosystem services through inspections of the species inventory is a major aspect of ecological field studies. Ecosystem functions are often stable despite considerable species turnover. Using metatranscriptome analyses, we analyse a thus‐far unparalleled freshwater data set which comprises 21 mainland European freshwater lakes from the Sierra Nevada (Spain) to the Carpathian Mountains (Romania) and from northern Germany to the Apennines (Italy) and covers an altitudinal range from 38 m above sea level (a.s.l) to 3110 m a.s.l. The dominant taxa were Chlorophyta and streptophytic algae, Ciliophora, Bacillariophyta and Chrysophyta. Metatranscriptomics provided insights into differences in community composition and into functional diversity via the relative share of taxa to the overall read abundance of distinct functional genes on the ecosystem level. The dominant metabolic pathways in terms of the fraction of expressed sequences in the cDNA libraries were affiliated with primary metabolism, specifically oxidative phosphorylation, photosynthesis and the TCA cycle. Our analyses indicate that community composition is a good first proxy for the analysis of ecosystem functions. However, differential gene regulation modifies the relative importance of taxa in distinct pathways. Whereas taxon composition varies considerably between lakes, the relative importance of distinct metabolic pathways is much more stable, indicating that ecosystem functioning is buffered against shifts in community composition through a functional redundancy of taxa.